Characterization of the polyhydroxyalkanoate (PHA) synthase from Ideonella sakaiensis, a bacterium that is capable of degrading and assimilating poly(ethylene terephthalate). (December 2022) - Tan, Hua Tiang; Chek, Min Fey; Neoh, Soon Zher; Ang, Shaik Ling; Yoshida, Shosuke; Hakoshima, Toshio; Sudesh, Kumar
Highlights: Characterization of PhaC from Ideonella sakaiensis 201-F6, a bacterium that is capable of degrading and assimilating PET. PhaC Is polymerizes five types of monomers: 3HB, 3HV, 4HB, 5HV and 3H4MV. Provides insights into the substrate specificity of PhaC Is, which is important for the metabolic engineering of I. sakaiensis that produces various types of PHA from PET. ABSTRACT: Ideonella sakaiensis 201-F6 is a bacterium capable of degrading and assimilating poly(ethylene terephthalate) (PET). A recent study revealed its capability in accumulating intracellular polyhydroxyalkanoate (PHA) at high levels using PET as a carbon source. The finding demonstrated that I. sakaiensis can mediate the direct conversion of non-biodegradable PET into environment-friendly PHA, providing a new approach for PET recycling. The PHA synthase gene of I. sakaiensis ( phaC Is ) was characterized in this study. Phylogenetic analysis of the PhaC protein sequences indicated PhaC Is belong to class I PhaC. To carry out in vivo characterization of PhaC Is, phaC Is was cloned and heterologously expressed in a PHA-negative mutant strain Cupriavidus necator PHB⁻4. The heterologous expression of the PhaC Is in PHB⁻4/pBBR1- C Is resulted in poly(3-hydroxybutyrate) [P(3HB)] accumulation of up to 71 wt% of the cell dry weight. In addition, the PhaC Is was shown to be able to polymerize 5 types of monomers, 3-hydroxybutyrate (3HB), 3-hydroxyvalerate (3HV), 4-hydroxybutyrate (4HB), 5-hydroxyvalerate (5HV), and 3-hydroxy-4-methylvalerate (3H4MV). In vitro enzymatic assay showed that PhaC Is was capable of catalyzing ( R )-3HB-CoA with a specific activity of 11.6 ± 0.6 nmol/min/mg and displayed an initial lag-phase. This study provides a basic information of PhaC Is that allows us to create variants applied for the metabolic engineering of I. sakaiensis that produces various types of PHA from PET.